الصنعة البديعية عند أحمد شوقي: دراسة تحليلية بلاغية لقصيدة "غاندي بطل الهند": The Art of Embellishments in the Poems of Ahmed Shawqi: An Analytical Rhetorical Study of his Poem "Gandhi Batal al-Hind" (Al Basirah, 2023)
The embellishment elements are the most important in achieving internal rhyme in Arabic poems because the value of poetry is based on the impact it has on the minds of readers and listeners through its musical structure. As a result, this study focuses on Ahmed Shawqi's poem "Gandhi Hero of India," with the objective of revealing the rhythmic and semantic functions of each of the rhetorical styles jinās, ṭibāq, tawāzī al tarkībī, and Taqsīm. This study adopted the analytical method, which analyzes the poetic verses according to the science of Badīʿ. The importance of the study is reflected in the fact that it sheds light on the extent to which the poet invests these literary devices in displaying images and emotions consistent with the nature of the text. The study concluded that the poet used al jinās al nāqiṣ in its most prominent patterns, the ṭibāq in its linguistic and contextual forms, and he also distributed the two words of these two literary styles between the two halves of the poetic verse, which strengthens the poem rhythmically and semantically. It also concluded that the complete and partial grammatical parallelism on the vertical and horizontal levels provided the poem with a distinct rhythm and semantic richness, in addition to the phenomenon of al Taqsīm al ʿaḍūḍī which played a role in moving the internal rhyme that drew readers' attention to the text's content.
Keywords: Ahmed Shawqi; Gandhi; Jinās; Ṭibāq; Tawāzī al tarkībī; Taqsīm al ʿaḍūḍī